The establishment of isothermal amplification and lateral flow device for detection of salmonella typhi and salmonella paratyphi A - Hanaphi, Roziana Mohamed (2020)
S. Typhi and S. Paratyphi A are the etiological agents of enteric fever and the diseases still affect low- and middle-income countries. Human is the only host for these bacteria and is easily transmitted via the oral route from the consumption of contaminated food and water. Currently, no carrier detection method is available in the market as developed molecular methods are limited to only lab-based research. Thus, a molecular-based method of isothermal amplification was chosen in this study to overcome the limitation of laborious work of the gold standard culture method and a high level of cross-reactivity in the serological method. Two detection assays were developed, namely rapid and simple assays through a combination of cross priming amplification (CPA) and lateral flow assay (LFA) to detect the presence of S. Typhi (known as Rapid isothermal TyphiAmp -LFA assay) and S. Paratyphi A (known as Rapid isothermal ParatyphiAmp -LFA assay). Six specific primers were designed for both assays within the targeted genes of staG of S. Typhi and intergenic region (SSPAI) between SSPA1723a and SSPA1724 of S. Paratyphi A. Three pairs of primers for each target were designed, including displacement primers, cross primers and detector primers. The primers assisted in displacement and amplification activities with the help of Bst DNA polymerase enzyme. The forward and reverse detector primers were labelled with biotin and FAM at 5’ ends respectively. The amplification assay works best at 63°C for 1 hour and followed by detection using lateral flow strip for 15 minutes. CPA assay for both S. Typhi and S. Paratyphi A demonstrated high specificity for both targeted bacteria detection on DNA of bacteria isolates of 30 S. Typhi, 30 S. Paratyphi A, 30 Salmonella serovars and 30 non-Salmonella bacteria. The limit of detection of the CPA for S. Typhi assay was 1 fg of genomic templates and 101 CFU/ml in bacteria culture, while, the CPA for S. Paratyphi A assay was 10 fg of genomic templates and 103 CFU/ml in bacteria culture. The results obtained were consistent for both S. Typhi and S. Paratyphi A assays for the detection method with agarose gel electrophoresis (AGE) and LFA. The sensitivity and specificity of both assays were effective when tested with 54 spiked-stool samples, 56 water samples from endemic areas and three stool samples of suspected carriers. The final form of lyophilised CPA reagents was obtained provided ready-to-use reagents together with lateral flow strips for limited resource settings and transportation without a cold chain. The stability testing of both assays in different storage temperatures of 4°C, 25°C, 37°C and 45°C revealed the shelf-life of three to four months when tested in 30 days storage. As a conclusion, the CPA was effective in the detection of S. Typhi and S. Paratyphi A, which was ideal for limited-resource settings with rapid detection, simple procedure and equipment, and easy readout of the assay results using LFA.